"Conocimiento de madres primíparas sobre alimentación complementaria y estado nutricional del lactante. Puesto de Salud Puente Piedra - Huamachuco, 2013" - Campos Reyes, Sandy Tania (2013)
This research is a descriptive correlational cross-sectional, was conducted at the Health Post Puente Piedra, Huamachuco District, 2013, in order to determine the relationship between the level of knowledge of first-time mothers on complementary feeding and infant nutritional status.The sample consisted of 116 first-time mothers with their infants. Data collection was obtained by the instruments: Survey time mothers knowledge on complementary feeding and tool to assess the nutritional status of the infant. The data were tabulated, processed in SPSS version 19 and presented in simple tables double entry with numerical frequencies and percentages, as well as graphics. The analysis of the relationship between the level of knowledge and nutritional status, was performed by independent test criteria Chi square (X2). Finding the following results: The level of knowledge on complementary feeding time mothers is average and 84 percent higher by 16 percent. The nutritional status of the infant as: Height for age: The 61 percent have normal size and 39 percent have short stature as: Weight for height: 98 percent of infants are found with a normal nutritional status and 2 percent overweight. The relationship between the level of knowledge of first-time mothers on complementary feeding and infant nutritional status as: Height for age is significant, and no significant relationship was found by: weight for height.